Liquid Crystals Phase Transitions and AC-Calorimetry - Sigdel, Krishna P. (Himalayan Physics, 2011)
Liquid crystal is a delicate and beautiful phase of matter showing the order in between liquid and crystals. They have different phases and phase transitions. A powerful tool called AC calorimetry can be used to characterize the different phases and phase transitions. In this article, use of ac-calorimetry technique in liquid crystal phases and phase transitions is described. Key words: Liquid and crystals; AC calorimetry The Himalayan Physics Vol.1, No.1, May, 2010 Page: 25-31 Uploaded Date: 28 July, 2011